2011
DOI: 10.1515/astro-2017-0273
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Automatic Estimation of Time Delays of Gravitational Lenses

Abstract: Estimation of time delays from a noisy and gapped data is one of the simplest data analysis problems in astronomy by its formulation. But as history of real experiments show, the work with observed data sets can be quite complex and evolved. By analysing in detail previous attempts to build delay estimation algorithms we try to develop an automatic and robust procedure to perform the task. To evaluate and compare different variants of the algorithms we use real observed data sets which have been objects of pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Monitoring in the optical requires a long baseline or high photometric precision to overcome systematic variations due to microlensing by stars in the lensing galaxy that could be mistaken as the background source intrinsic variability (e.g., Tewes et al 2013b;Sluse & Tewes 2014). Curve-shifting methods have been developed to measure the time delays from the light curves (e.g., Press et al 1992;Pelt et al 1996;Fassnacht et al 2002;Harva & Raychaudhury 2008;Hirv et al 2011;Morgan et al 2008;Tewes et al 2013a;Hojjati et al 2013). A recent time-delay challenge showed that some of the methods can recover accurately the time delays in a blind test (Dobler et al 2015;Liao et al 2015), particularly the methods we use from the COSMOGRAIL collaboration (e.g., Tewes et al 2013a;Bonvin et al 2016).…”
Section: Observational Requirements Of the Time-delay Methodsmentioning
confidence: 99%
“…Monitoring in the optical requires a long baseline or high photometric precision to overcome systematic variations due to microlensing by stars in the lensing galaxy that could be mistaken as the background source intrinsic variability (e.g., Tewes et al 2013b;Sluse & Tewes 2014). Curve-shifting methods have been developed to measure the time delays from the light curves (e.g., Press et al 1992;Pelt et al 1996;Fassnacht et al 2002;Harva & Raychaudhury 2008;Hirv et al 2011;Morgan et al 2008;Tewes et al 2013a;Hojjati et al 2013). A recent time-delay challenge showed that some of the methods can recover accurately the time delays in a blind test (Dobler et al 2015;Liao et al 2015), particularly the methods we use from the COSMOGRAIL collaboration (e.g., Tewes et al 2013a;Bonvin et al 2016).…”
Section: Observational Requirements Of the Time-delay Methodsmentioning
confidence: 99%
“…A broad range of curve-shifting algorithms have been developed in the past to measure time delays between light curves (e.g. Press et al 1992;Pelt et al 1994;Kelly et al 2009;Hirv et al 2011;Hojjati et al 2013;Hojjati & Linder 2014;Aghamousa & Shafieloo 2015). Efficient algorithms must be robust against photometric noise, coarse temporal sampling, season gaps and must also take into account the presence of microlensing caused by moving stars in the lensing galaxy.…”
Section: Time-delay Measurementsmentioning
confidence: 99%
“…Unevenly spaced data resulting from, for example, weather and/or observing time allocation, are a challenge for light-curve analysis. A number of techniques have been specially developed to utilize these multiple light curves of mirage images with unevenly sampled data (Edelson & Krolik 1988;Press et al 1992;Burud et al 2001;Pelt et al 1998;Pindor 2005;Scargle 1982;Roberts et al 1987;Geiger & Schneider 1996;Gürkan et al 2014;Hirv et al 2011).…”
Section: Time Delay Measurementmentioning
confidence: 99%